Pro-Poor Growth in Algeria: a Statistical Approach - bouakaz, iman; bahri, amira (Finance and Business Economies Review, 2022)
This research is concerned with studying the pro-poor growth by introducing the various theoretical approaches that addressed the pro-poor growth, and then analyzing the phenomenon of poverty and its most important characteristics in Algeria and determining the characteristics of disparity in the distribution of income in Algeria. The study also used few indicators to determine the extent to which growth favors the poor in Algeria. The most important findings of the study were that economic growth was modest in favor of the poor, and this favoritism was not the result of the fruits of economic growth, but rather as a result of the redistribution of income as a result of the expansion of public spending in Algeria, which depends on oil rents during the period 2000-2018